A patient with cancer and psoriasis – difficulties following oncology treatment - Biedka, Marta; Ziółkowska, Ewa; Makarewicz, Roman; Pietrusińska, Elżbieta; Kubiak, Maria (Contemporary Oncology/Współczesna Onkologia, 2009)
Psoriasis affects about 2–3% of the world’s population, with men and women being equally affected. Psoriasis tends to worsen during periods of stress, skin trauma, with the administration of certain drugs, and infections. Psoriasis is characterized by parakeratosis and thickening of the epidermis and is generally referred to as chronic plaque psoriasis. Its features include silvery, scaly, erthematous plaques, ordinarily found on the scalp, elbows, knees, and buttocks. Erythrodermic psoriasis, the most severe form of disease, is characterized by diffuse erytrema and scaling, often accompanied by fever, chills, and malaise. Patients with serve cases of erythrodermic psoriasis may have hypothermia and hypoalbuminemia secondary to skin exfoliation. Bet-ween 10–17% of patients with generalized pustular psoriasis suffer from arthralgias, myalgias, and mucosal lesions. Finally, up to 20% of patients with psoriasis have psoriasis arthritis. The aim of this article is to demonstrate posibility of exacerbation of psoriasis following oncology treatment.